Determinants of Islamic Human Development Index: Evidence from OIC Developing Countries - Sukran; Fasiha (Jurnal Ekonomi Syariah Teori dan Terapan, 2024)
The purpose of this study is to assess how government spending and governance relate to the Islamic Human Development Index (IHDI) in developing countries that are members of the Organization of Islamic Cooperation (OIC). Panel data regression is used in this work to mix cross-sectional and time series data from 2011 to 2020. The best panel data model for this investigation was determined to be the Random Effect Model (REM). The study's findings demonstrate that the Islamic Human Development Index (IHDI) is significantly benefited by both government spending and good governance. Hence, efficient government spending and sound administration are crucial for all nations, even the emerging nations of the Organization of Islamic Cooperation. Partially, the variable of government governance is only the rule of law which has a significant positive effect on the Islamic Human Development Index (IHDI). This indicates that the application of a good and effective rule of law will enhance human development which may have implications for improving a country's economy